Analisis Kesiapan Masyarakat Kecamatan Sepaku dan Samboja Terhadap Rencana Pemindahan Ibu Kota Negara Indonesia - Dewi, Maulida Rachmalia; Syafitri, Elin Diyah; Dewanti, Ajeng Nugrahaning (Jurnal Pembangunan Wilayah dan Kota, 2020)
The relocation of the national capital is national development that has a positive impact and benefits on the people in it. Sustainable results in national development can occur if the community is actively involved in its development. Community involvement is related to the community readiness in Kecamatan Sepaku and Samboja in dealing with the relocation of the Indonesia‟s national capital. If the community is not ready, it can affect the condition of the community itself. The highest level of community readiness in dealing with issues is that the community involved and able to evaluate the program that has been prepared.. However, the condition of the community in Kecamatan Sepaku and Kecamatan Samboja is not yet known towards the planned relocation of the national capital. Therefore, this study aims to analyze the level of readiness of Kecamatan Sepaku and Kecamatan Samboja towards of the relocation of the national capital. Analysis of the level of community readiness using the community readiness model. It is known that the final value of the community readiness in Kecamatan Sepaku is 3 (vague awareness) and in Kecamatan Samboja is 2 (denial / resistance).